Rezidivierendes DMEK-Versagen - Matar, C. (Ophthalmologe, 2020)
We report a Patient with Fuchs dystrophy who underwent three Descemet Membrane Endothelial Keratoplasties (DMEK) caused by recurrent graft failure with raise in intraocular pressure and cystoid macular edema. At the third DMEK, herpes was detected in the anterior chamber tap and an adequate therapy was initiated. At the 6 months follow-up the cornea remained clear, visual acuity was 0.8, intraocular pressure was within normal range and macular edema regressed completely. Either a latent Herpes simplex Virus (HSV) infection of the patient was reactivated or an infected donor lamella was transplanted with donor-to-host-to-donor ping-pong transmission.